Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1055/s-0039-1693030
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disorders in Children: An Observational Study in a Tertiary Care Center in North India

Abstract: Movement disorders (MDs) are disorders of pathological movements that cannot be fully initiated, modulated, or interrupted voluntarily. Spectrum and etiology of MDs are likely to vary with geographical location, but there are few studies on pediatric MDs from India, and severity of the disease is not well documented. Response to treatment of MDs is often unpredictable. Objective of the study was to describe the relative prevalence, types, severity, etiology, and response to treatment of pediatric MDs as seen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…5 Pandey et al reported dystonia in 24.7% of cases in his study on movement disorders in children on outpatient basis. 1 Andrade et al reported 46.2% to have secondary dystonia, with tardive dystonia being the most common etiology followed by perinatal cerebral injury. 6 In our study, Wilson's disease constituted 30.8% of dystonia cases, and drugs were the etiology in 15%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Pandey et al reported dystonia in 24.7% of cases in his study on movement disorders in children on outpatient basis. 1 Andrade et al reported 46.2% to have secondary dystonia, with tardive dystonia being the most common etiology followed by perinatal cerebral injury. 6 In our study, Wilson's disease constituted 30.8% of dystonia cases, and drugs were the etiology in 15%.…”
Section: Discussionmentioning
confidence: 99%
“…The study was intended to find the spectrum of movement disorders admitted at a tertiary care hospital in the neurology department. Previous studies have mainly focused on cases attending the outpatient clinics, 1 2 although there have been studies on spectrum of movement disorders in pediatric inpatients. 3 A study was also conducted by Kwon et al on clinical characteristics of movement disorders in inpatients as part of neurologic consultations from other departments.…”
Section: Discussionmentioning
confidence: 99%